Challenges and Implementation of Environmental Law in Sustainable Development in the Coal Mining Industry Area - Suryaningsi Suryaningsi (Novateur Publications, 2023)
The obligation to carry out post-mining land rehabilitation and waste water management are two important aspects because they have the potential to reduce the negative impact of mining on the environment (Joni, 2020). Post-mining land rehabilitation is the process of restoring ex-mining land so that it can function again or approach its natural condition, expressly stipulated in the Regulation of the Minister of Energy and Mineral Resources.Source One Minerals No. 7 of 2014 concerning the implementation of Reclamation and Post Mining in Mineral and Coal Mining Business Activities. Through this regulation, it is also recommended to do bSome common steps in post-mining land rehabilitation include: The initial phase involves the removal of mined material such as rock, disturbed soil and other debris. Then, the topsoil that is removed will be replaced with fertile soil
Keywords: Challenges; Implementation of Environmental Law; Sustainable Development